2011
DOI: 10.1007/978-3-642-23957-1_31
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Discovery and Risk Prediction for Chronic Diseases: An Integrated Approach

Abstract: Abstract.A novel ontology based type 2 diabetes risk analysis system framework is described, which allows the creation of global knowledge representation (ontology) and personalized modeling for a decision support system. A computerized model focusing on organizing knowledge related to three chronic diseases and genes has been developed in an ontological representation that is able to identify interrelationships for the ontology-based personalized risk evaluation for chronic diseases. The personalized modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…14,15 The main objective of personalized modeling is to create a model for each patient (sample), which is able to reveal the most important information specifically for each sample, focusing attention on the individual patient (sample) rather than simply on the global problem space. 16,17 Previous works have reported that personalized modeling can produce better classification results than those obtained from classical global modeling, 14,16,18 making it more appropriate to build clinical decision support systems for new patients. The framework proposed by Fiasché et al 11,19 used a "personalized" wrapping method, a PMGS described in detail in recent papers 20,21 for gene expression data analysis, integrating new data with the existing models; the block diagram is reported in Figure 1.…”
Section: Personalized Modeling For Identification Of Target Genes In mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The main objective of personalized modeling is to create a model for each patient (sample), which is able to reveal the most important information specifically for each sample, focusing attention on the individual patient (sample) rather than simply on the global problem space. 16,17 Previous works have reported that personalized modeling can produce better classification results than those obtained from classical global modeling, 14,16,18 making it more appropriate to build clinical decision support systems for new patients. The framework proposed by Fiasché et al 11,19 used a "personalized" wrapping method, a PMGS described in detail in recent papers 20,21 for gene expression data analysis, integrating new data with the existing models; the block diagram is reported in Figure 1.…”
Section: Personalized Modeling For Identification Of Target Genes In mentioning
confidence: 99%
“…Since simple statistical analysis or classical data-mining techniques failed to identify a specific gene pattern, we used computational intelligence methods according to previously published algorithms. 17,19,20 The PMGS approach was applied to the data obtained from the TLDA-card to identify a group of genes to represent the data set. In our framework the most important genes selected for each patient may differ (personalized subset), but during our analysis, it was evident that for each run, four genes were always present in the entire subset of patients who did develop aGvHD.…”
Section: Personalized Modeling-based Gene Selection Identified Foxp3mentioning
confidence: 99%
“…Ontological reasoning engines are being used to add deduction capabilities to these systems [62]. The commonest use of decision support is the diagnosis of disease decision support and it is increasingly used for detecting the risk of disease, prescribing or other intervention decisions and prevention [63][64][65].…”
Section: Decision Supportmentioning
confidence: 99%
“…We need a formal representation of diabetes terminology, vocabulary and relationships to discover and extract, share, retrieve and reuse knowledge. Ontology is a technique to store semantic information and facilitate manipulating with data by applying different methods such as analysis and algorithms ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The different stakeholders will access and share the most recent medical knowledge due to the scalability of the ontology and the frequent updates that will deliver. More advance queries could be applied by using Simple Protocol and RDF Query Language (SPARQL) ( 2 , 5 ) and intelligent algorithms for clustering, classifications and generate association rules in many applications ( 3 ).…”
Section: Introductionmentioning
confidence: 99%